3D position estimation of badminton shuttle using unsynchronized multiple-view videosübersetzter Titel (DE) - Shishido, H.; Kameda, Y.; Kitahara, I.; Ohta, Y. (AH '16: Proceedings of the 7th Augmented Human International Conference 2016, 2016)
In this paper, we introduce a method to estimate 3D position of a badminton shuttle using unsynchronized multiple-view videos. The research of object tracking for sports is conducted as an application of Computer Vision to improve the tactics involved with such sports. This paper proposes a technique to stably estimate object's position by using motion blur that used be considered as observational noise in the ordinary works. Badminton shuttle has a large variation of the moving speed, the motion trajectory is unpredictable and moreover the observation size is very small. Thus, it cannot be grasped correctly with human eyes. We apply our proposed technique to badminton shuttle tracking to confirm the ability of our method to enhance the human vision. We also consider that there is some contribution to augment sports in future.